The Pontifical Thought of Jan Van Bragt (1928-2007) - Heisig, James W. (Bulletin of the Nanzan Institute for Religion & Culture, 2008)
This year’s annual conference of the Japan Society for Buddhist-Christian Studies (東西宗教交流学会) paid tribute to one of its founding fathers and long-time participant, Jan Van Bragt, by opening with special lectures on his writings and thought. The following is an English rendition of the first of those lectures, presenting an overview of his thought. It was followed by Nishimura Eshin’s analysis of Van Bragt’s critiques of Nishitani’s philosophy. The Japanese text of both lectures will appear in the 2008 edition of the Society’s journal『東西宗教研究』. For a comprehensive list of Van Bragt’s published writings see: http://www.nanzan-u.ac.jp/SHUBUNKEN/ staff/Van_Bragt.htm.